2021
DOI: 10.1177/0018726721992849
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the psychologically detrimental effects of supervisor undermining: Joint effects of voice and political skill

Abstract: It is of growing concern that supervisors sometimes engage in destructive leadership behavior to undermine their subordinates, which exacts a psychological toll on these employees. How can employees mitigate and overcome the adverse psychological effects of supervisor undermining? Invoking theories of personal agency and social competencies, this study addresses this important question by examining the effectiveness of employee voice in buffering the adverse effects of supervisor undermining on employee work-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 97 publications
4
16
0
Order By: Relevance
“…Finally, future research should extend our study by incorporating other psychological and leadership resources such as psychological resilience (Fletcher & Sarkar, 2013), hardiness (Funk, 1992), self‐talk (Tod et al., 2011), leader's social support and undermining (Duffy et al., 2002) that may also affect how individuals deal with the impact of a pandemic upon their mental health status and work performance during the COVID‐19 pandemic. Focussing on these psychological and leadership behaviours is also consistent with our guiding theory given COR theory suggests that some people can remain resilient and hopeful despite facing mass trauma (Doane et al., 2012; Hobfoll, 1998) and that leadership represents a critical source of support as well as a source of draining experience (Duffy et al., 2002; Gerpott et al., 2020; Sun et al., 2021). Nonetheless, we highlight that we focus on visionary leadership in the current study for both theoretical and practical reasons.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, future research should extend our study by incorporating other psychological and leadership resources such as psychological resilience (Fletcher & Sarkar, 2013), hardiness (Funk, 1992), self‐talk (Tod et al., 2011), leader's social support and undermining (Duffy et al., 2002) that may also affect how individuals deal with the impact of a pandemic upon their mental health status and work performance during the COVID‐19 pandemic. Focussing on these psychological and leadership behaviours is also consistent with our guiding theory given COR theory suggests that some people can remain resilient and hopeful despite facing mass trauma (Doane et al., 2012; Hobfoll, 1998) and that leadership represents a critical source of support as well as a source of draining experience (Duffy et al., 2002; Gerpott et al., 2020; Sun et al., 2021). Nonetheless, we highlight that we focus on visionary leadership in the current study for both theoretical and practical reasons.…”
Section: Discussionsupporting
confidence: 63%
“…In general, for example, it has been widely established that politically skilled individuals experience job satisfaction and organizational commitment at work (Epitropaki et al, 2016;Hayek et al, 2018;Li et al, 2017;Munyon et al, 2015); even when distrust in management is accounted for (Gallagher et al, 2016). Political skill also indicates a positive association with career satisfaction (Fidan and Koç, 2020), whereas it demonstrates a negative association with turnover intentions (Garc ıa-Chas et al, 2019;Sun et al, 2022).…”
Section: Meta-theoretical Framework Of the Effects Of Political Skillmentioning
confidence: 99%
“…Accordingly, it's been reported that politically skilled individuals thrive in central network positions as they are better able to manage associated role ambiguities (Cullen et al, 2018). Owing to their ability to understand themselves and others at work (Frieder et al, 2019), politically skilled individuals have also been found to be able to cope with adversity in work environments, such as workplace incivility (Karatepe et al, 2019;De Clercq et al, 2019), workplace aggression (Zhou et al, 2015), supervisor undermining (Sun et al, 2022) and abusive supervision (Li et al, 2016;Holmquist, 2020).…”
Section: Meta-theoretical Framework Of the Effects Of Political Skillmentioning
confidence: 99%
See 1 more Smart Citation
“…High political skilled individuals possess the ability to effectively influence others' behaviours and attitudes, including toward them (Brouer et al, 2011). Further, research indicates that political skill facilitates the success of individual agentic behaviours (such as through opportunity recognition and capitalization; Sun et al, 2021;Wihler et al, 2017). Thus, they may believe that they will be able to frame remedial voicing in a positive light, for example as a constructive approach to resolving interpersonal differences and enhancing congeniality in the workplace and may influence others to maintain a positive impression of them as congenial rather than confrontational.…”
Section: H1mentioning
confidence: 99%